Local non-equilibrium effect on the growth kinetics of crystals. (15th April 2019) - Galenko, P.K.; Ankudinov, V.
Abstract: A phase field model for small and large driving forces on solidification and melting of a pure metal or binary alloy is formulated. A traveling wave solution of the phase field equation predicts the non-linear behavior in the velocity of the crystal/liquid interface at the large driving force. This non-linearity has the dependence of velocity with saturation or exhibiting the velocity with maximum at a fixed undercooling/superheating. The predicted velocity is compared with the molecular dynamics simulation data for pure Fe that confirms a crucial role of local non-equilibrium in the form of relaxation of gradient flow in the quantitative description of the crystal growth kinetics. Graphical abstract: Image 1